Respostas da mastofauna terrestre não voadora de médio e grande porte ao manejo com fogo controlado - Silveira, Heluisa Martins (2017)
In pyrophytic environments, as Cerrado, the absence of fire can cause decharacterization and degradation of its composition, which compromise the conservation of local biodiversity. Each species respond differently to the fire, depending on its intensity, frequency and extension. Non-flying mammals are important ecosystem modeler agents, because they act in different ways in the environment and maintain the balance of the food web. Thus, this study aimed to evaluate the responses of non-volant terrestrial mammals of Cerrado against the prescribed fire management in Parque Estadual do Cerrado, PR, Brazil. Two treatments were studied; one of them was treated with controlled fire and the other one not. The method used consisted of vestigial analysis, photographic traps of mammals that appeared in both plots during the period of 1 year. The data were analyzed using the absolute occurrence frequencies and multivariate analysis. Twelve species were surveyed: C. thous, C. brachyurus, D. novemcinctus, Lagomorpha, L. tigrinus, L. europaeus, M. gouazoubira, M. tridactyla, N. nasua, O. bezoarticus, Rodentia and T. tetradactyla. Of these, generalists herbivorous were the ones that most frequently to prescribed fire management, due to the more palatable and nutritive food. Generalists predators seemed to be distributed in sites where preys were more likely to be found. Prescribed fire must be use as a management technique in conservation units that showed phytophysionomies of Cerrado. Therefore, it is advisable reviews in management plans of conservation units for protection of the Cerrado biome aimed to update the best strategies for conservation of its natural resources.